Histopathology of the pulp of primary molars with active and arrested dentinal caries - Di Nicolo, Rebeca [UNESP]; Guedes-Pinto, Antonio Carlos [UNESP]; Carvalho, Yasmin Rodarte [UNESP] (My University, 2000)
The purpose of this study was to compare the histological appearance of the pulp of human primary molars with active and arrested lesions. The sample consisted of 36 primary molars (18 with active lesions and 18 with arrested lesions) extracted from 35 children between 5 to 9 years of age. The histological diagnosis was classified in normal pulp, transitional stage, partial pulpitis, total pulpitis and total necrosis, and then subdivided in three subgroups: treatable, untreatable and questionable. Results showed that normal pulp or transitional stage (treatable category) was diagnosed in 50% of teeth with arrested lesions, compared to 11.1% of teeth with active lesions. Partial pulpitis (questionable category) was present in 38.8% with arrested lesions compared to 22.2% with active lesions. Total pulpitis and total necrosis (untreatable category) was diagnosed in 11.2% with arrested lesions compared to 66.7% with active lesions. The observed frequencies of histological categories between both groups were statistically significant (P < 0.05). Histologically, pulp reaction under active and arrested lesions in primary molars revealed the formation of a basophilic calcio-traumatic line at the junction of the primary and reparative dentin, formation of reparative dentin and a regular odontoblastic layer in 60% of the cases. Results indicated that the type of lesion (active or arrested) is a good indicator of the histological status of the pulp.